1998
DOI: 10.1111/1469-8986.3540452
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulus modality and task condition on blink startle modification and on electrodermal responses

Abstract: Participants in Experiments 1 and 2 performed a discrimination and counting task to assess the effect of lead stimulus modality on attentional modification of the acoustic startle reflex. Modality of the discrimination stimuli was changed across subjects. Electrodermal responses were larger during task-relevant stimuli than during task-irrelevant stimuli in all conditions. Larger blink magnitude facilitation was found during auditory and visual task-relevant stimuli, but not for tactile stimuli. Experiment 3 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
29
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 6 publications
(6 reference statements)
7
29
2
Order By: Relevance
“…found prestimulus augmentation of blink at a 2,000-msec SOA that was stable over the testing session, a finding replicated in a second experiment. Lipp, Siddle, and Dall (1998) found that the blink reflex was augmented by acoustic and visual, but not vibrotactile,prestimuli presented at SOAs of 3,500 and 4,500 msec. Other studies, however, have not reported clear augmentation with sustained prestimuli.…”
mentioning
confidence: 88%
“…found prestimulus augmentation of blink at a 2,000-msec SOA that was stable over the testing session, a finding replicated in a second experiment. Lipp, Siddle, and Dall (1998) found that the blink reflex was augmented by acoustic and visual, but not vibrotactile,prestimuli presented at SOAs of 3,500 and 4,500 msec. Other studies, however, have not reported clear augmentation with sustained prestimuli.…”
mentioning
confidence: 88%
“…The longer than usual lead stimulus has been 7 s in duration, compared to the usual duration of 5 s. In the research reported to date, the stimulus modality of the lead stimulus has been varied and an acoustic blink‐eliciting stimulus has been used. It has been reported that blink magnitude is larger and blink latency is shorter during task‐relevant lead stimuli than during task‐irrelevant lead stimuli when the lead stimuli are presented in the acoustic and visual modalities (Böhmelt, Schell, & Dawson, 1999; Filion et al, 1993; Lipp, Neumann, Pretorius, & McHugh, 2003; Lipp, Siddle, & Dall, 1997, 1998). No difference between task‐relevant and task‐irrelevant lead stimuli has been found when tactile lead stimuli are used (Lipp et al, 1998).…”
mentioning
confidence: 99%
“…It has been reported that blink magnitude is larger and blink latency is shorter during task‐relevant lead stimuli than during task‐irrelevant lead stimuli when the lead stimuli are presented in the acoustic and visual modalities (Böhmelt, Schell, & Dawson, 1999; Filion et al, 1993; Lipp, Neumann, Pretorius, & McHugh, 2003; Lipp, Siddle, & Dall, 1997, 1998). No difference between task‐relevant and task‐irrelevant lead stimuli has been found when tactile lead stimuli are used (Lipp et al, 1998). This null finding may reflect that the tactile lead stimulus used in previous research has consisted of a discontinuous vibration pulsed at a frequency of 50 Hz.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Modality-specific blink modulation has not been found during some types of tasks. These have included a discrimination and counting task (Lipp, Siddle, & Dall, 1998), an intermodality change task (Lipp, Siddle, & Dall, 2000b), and a reaction time task (Lipp, Siddle, & Dall, 2000a).…”
Section: Spontaneous and Reflexivementioning
confidence: 99%